2013
DOI: 10.7860/jcdr/2013/5325.3145
|View full text |Cite
|
Sign up to set email alerts
|

Postmenopausal Intraocular Pressure Changes in South Indian Females

Abstract: The higher IOP in postmenopausal women could be ascribed to dwindling levels of oestrogen and progesterone after menopause, which could act by altering any/several components of the IOP regulating mechanisms. A large body size, as was indicated by BMI, was associated with additional increases in IOP. The present study, therefore, provides further insights into the interactions between BMI and paucity of sex hormones in influencing the IOP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Our finding that OVX decreased outflow facility is consistent with both the modest elevations in IOP (1–3 mm Hg) measured in postmenopausal women 7 , 9 12 and data suggesting that estrogen therapy increases outflow facility. 12 …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our finding that OVX decreased outflow facility is consistent with both the modest elevations in IOP (1–3 mm Hg) measured in postmenopausal women 7 , 9 12 and data suggesting that estrogen therapy increases outflow facility. 12 …”
Section: Discussionsupporting
confidence: 88%
“…Menopause is associated with modest IOP elevations, as IOP in postmenopausal women is 1 to 3 mm Hg higher than in age-matched premenopausal women. 7 , 8 Further, estrogen therapy in postmenopausal women causes a 0.5- to 3-mm Hg decrease in IOP. 9 11 Aqueous outflow facility is the major determinant of IOP, and estrogen treatment has been shown to increase outflow facility in female patients 12 ; however, it is unknown whether menopause or age at menopause affects outflow facility.…”
mentioning
confidence: 99%
“…Research on the effects of progesterone on ocular disease in humans is sparse and often anecdotal. A variety of ocular changes have been shown to take place during times of hormonal fluctuation (Avitabile et al, 2007; Errera et al, 2013; Grant and Chung, 2013; Panchami et al, 2013; Yucel et al, 2005; Ziai et al, 1994), and gender differences are observed in rates of DR, glaucoma, AMD, dry eye, and cataracts (Wickham et al, 2000). Progesterone administered exogenously has been shown to reduce intraocular pressure, suggesting potential benefit for glaucoma (Obal, 1950; Posthumus, 1952).…”
Section: Progesteronementioning
confidence: 99%
“…Postmenopausal women have a 1.5-3.5 mmHg higher IOP compared to age-matched premenopausal women (Panchami et al 2013;Qureshi 1996). However, postmenopausal women receiving hormone replacement therapy containing estrogen had a 0.5-3 mmHg lower IOP compared to postmenopausal women not receiving hormone replacement therapy (Vajaranant and Pasquale 2012;Altintas et al 2004;Vajaranant et al 2016;Affinito et al 2003).…”
Section: Menopause and Intraocular Pressurementioning
confidence: 95%